PRAKTIK DIFERENSIASI PEMBELAJARAN IPAS DENGAN DUKUNGAN MEDIA DIGITAL DAN PROYEK LINGKUNGAN DI SEKOLAH DASAR - Mutiara Kartika Sari; Putri Dani Deskustya Ningrum; Salsabila Putri Nur Aini; Muhammad Imaduddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to describe the practice of science and science learning differentiation with the support of digital media and environmental projects in class V of SDN Magetan 02. This research uses descriptive qualitative methods with data collection techniques in the form of observation, interviews and documentation. The research subjects were fifth grade teachers who implemented science and science learning in the Merdeka Curriculum. The research results show that the practice of learning differentiation is carried out through the formation of heterogeneous learning groups, the application of peer tutoring, as well as providing remedial and enrichment according to students' learning needs. In supporting the learning process, teachers use digital media in the form of Digital Interactive Boards (PID) to help students understand the science material in a more visual and interactive way. Apart from that, learning is also developed through environmental projects in the form of using used goods into plant pots to foster students' creativity and environmental awareness. Thus, science and science learning differentiation practices supported by digital media and environmental projects can help create learning that is more adaptive, contextual, and in accordance with the characteristics of students in elementary schools.